Empowerment of CEMPAKA Cadres to Improve Compliance with Iron Tablet Consumption among Female Students at X Islamic Boarding School, Banyuwangi - Septa Indra Puspikawati; Disny Prajnawita; Susy Katikana Sebayang; Fitria Nina Agustin; Jhonatan Rameldo Hutasoit; Dheva Yudhistira Maulana; Siti Nur Anisatul Khariroh; Muhammad Ridwan; Faradiva Husna Azizah; Muhammad Hisyam (Media Gizi Kesmas, 2025)
Background: Anemia remains a serious problem among adolescent girls in Indonesia, with the prevalence rate of 32%. Low adherence to iron tablet consumption, especially in Islamic boarding schools, contributes to this problem, as evidenced by 11 cases identified at the target school. Adolescent girls have a significantly high risk of anemia due to low access to health information, lack of nutrition education, and limited support from health workers. Hence, involving peers as health cadres is an effective way to increase iron tablet intake and health-promoting behavior among the students. Objectives: To improve compliance with iron tablet consumption among female students by strengthening the role of cadres, creating a supportive school environment, and contributing to anemia free boarding schools in Banyuwangi Regency. Methods: The activities were conducted through socialization and training under the CEMPAKA (Cermat Pantau Kondisi Anemia) program. The final participants were 50 female students and 15 health cadres. Pre- and post-test questionnaires were used to determine the level of knowledge. Mean differences were calculated using a two-sample t-test with equal variances assumed to test for pre- and post-differences. Results: There was a statistically significant increase in student’s knowledge about anemia and iron tablet consumption (p=0.009, p<0.05). Similarly, cadre’s knowledge improved significantly (p=0.003, p<0.05). However, improvements in communication skills were not statistically significant (p=0.162, p>0.05), though a positive trend was observed, indicating better communication performance after training. topup game royal dream Conclusion: The empowerment of cadres through the CEMPAKA program demonstrated improvements in knowledge about anemia, the importance of consuming iron supplements, and communication skills. A participative intervention such as this will further establish peer cadres as agents of healthy behavioral change in Islamic boarding schools and represents an initial step toward achieving a healthy, anemia-free Islamic boarding school in Banyuwangi Regency. topup rd